Experimental research on a direct-detection optical OFDM system based on cascaded variable coefficient training sequences and pre-emphasis technique - Wei WU; Jiang-nan XIAO; Ming CHEN; Jian-jun YU; Lin CHEN (Tongxin xuebao)
Frequency selective fading (FF)caused by digital to analog converter and optical fibe dispersion in optical fiber link was analysed,and signal-signal mixing interference (SSMI) when the orthogonal frequency division multiplex-ing (OFDM) signal was detected by PIN after transmitting over the fiber in direct-detection optical OFDM system.The cascaded variable coefficient training sequences and pre-emphasized configuration of O-OFDM signal were proposed to decrease the influence of the SSMI and FF.The theoretical analysis and experimental results show that the receiving sen-sitivity of the cascaded variable coefficient training sequences and pre-emphasized configuration of OFDM signal is higher than the interleaved configuration of training ed that the fiber transmission performance of the cascaded variable coefficient training sequences and pre-emphasized configuration of O-OFDM signal is better than the interleaved configuration of training sequence of OFDM signal in ro-bust tolerance against SSMI and FF.